2019
DOI: 10.1167/iovs.19-27470
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the Genetic Landscape of Usher-Like Phenotypes

Abstract: PURPOSE. Usher syndrome (USH) is a rare disorder characterized by retinitis pigmentosa (RP) and sensorineural hearing loss. Several genes are responsible for the disease, but not all cases are explained by mutations in any of these, supporting the fact that there remain other unknown genes that have a role in the syndrome. We aimed to find the genetic cause of presumed USH patients lacking pathogenic mutations in the known USH genes. METHODS. Whole exome sequencing was performed on a priori USH-diagnosed subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…This includes variants in common USH genes which result in atypical USH phenotypes, complicating the paradigm of assigning certain USH genes to either USH1, USH2, or USH3 (Pennings et al 2004; Bashir et al 2010; Pérez-Carro et al 2018; Zhang et al 2018; D’Esposito et al 2019; Lee et al 2019; Valero et al 2019). Another study which used whole exome sequencing to screen clinically diagnosed USH patients who lacked pathogenic mutations in known USH genes found potentially causative mutations in a variety of hearing and retina-related non-USH genes, again highlighting the disconnection between clinical and molecular classifications (Fuster-García et al 2019). This is in line with data from the University of Iowa’s Genetic Eye-Ear Clinic, which found that the combination of expert clinical evaluation and molecular testing led to a change in diagnosis in 52% of deaf-blind families who presented to the clinic, 29% of who received molecularly confirmed final diagnoses of USH (Stiff et al 2020).…”
Section: New Directions In Usher Genotype-phenotype Classificationsmentioning
confidence: 99%
See 2 more Smart Citations
“…This includes variants in common USH genes which result in atypical USH phenotypes, complicating the paradigm of assigning certain USH genes to either USH1, USH2, or USH3 (Pennings et al 2004; Bashir et al 2010; Pérez-Carro et al 2018; Zhang et al 2018; D’Esposito et al 2019; Lee et al 2019; Valero et al 2019). Another study which used whole exome sequencing to screen clinically diagnosed USH patients who lacked pathogenic mutations in known USH genes found potentially causative mutations in a variety of hearing and retina-related non-USH genes, again highlighting the disconnection between clinical and molecular classifications (Fuster-García et al 2019). This is in line with data from the University of Iowa’s Genetic Eye-Ear Clinic, which found that the combination of expert clinical evaluation and molecular testing led to a change in diagnosis in 52% of deaf-blind families who presented to the clinic, 29% of who received molecularly confirmed final diagnoses of USH (Stiff et al 2020).…”
Section: New Directions In Usher Genotype-phenotype Classificationsmentioning
confidence: 99%
“…However, none of these treatment modalities address the pathophysiologic mechanisms underlying USH. A variety of gene therapy approaches to the inner ear and retina are being investigated, and research is ongoing to develop mutation-specific treatment modalities (Geleoc & El-Amraoui 2020). A currently recruiting trial for RP is investigating an intravitreal injection of an antisense oligonucleotide for mutation-specific treatment of the most common variants of exon 13 in the USH2A gene (ProQR, Stellar; Trial #NCT03780257).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Utilizing a combination of methods or a more comprehensive approach to genetic testing may increase the detection of bi- allelic pathogenic variants to above 90% (44,45). For example, including genes implicated in both non-syndromic hearing loss and retinal degenerations may reveal rare cases with a clinical presentation similar to that of USH but with biallelic variants in two different genes (45,46). Nonetheless, rare variants of hitherto unidentified genes for USH should be considered, noting that these likely account for a minority of patients.…”
Section: Genetic Heterogeneitymentioning
confidence: 99%
“…These three clinical subtypes are associated with nine causal genes encoding various proteins expressed in the inner ear and retina and playing key roles in auditory sensory cell development and function, and photoreceptor maintenance. However, a growing list of additional genes have been reported to be associated with a poorly defined clinical subtype called "atypical Usher syndrome" that does not meet the canonical criteria for the three recognized Usher syndrome subtypes (Bolz 2020;Castiglione and Moller 2022;Fuster-Garcia et al 2019;Nisenbaum et al 2021;Nolen et al 2020;Stiff et al 2020). Moreover, for each Usher syndrome-associated gene, Sedigheh Delmaghani and Aziz El-Amraoui are Joint senior.…”
Section: Introductionmentioning
confidence: 99%